# What number has a sum of 10 and a difference of 2?

## What number has a sum of 10 and a difference of 2?

Two composite numbers whose sum is 10 and difference 2: 6+4= 10, 6–4= 2, 6=2*3 and 4=2*2 —-the only possibility: 6 and 4.

What is the sum of all numbers up to 10?

55
1 is the smallest amongst the list of the first ten natural numbers. There are a total of 10 natural numbers in the list from 1 to 10. The sum of the first ten natural numbers, that is from 1 to 10 is 55.

What is the sum of 10 and the difference is 8?

Given, the sum of the numbers is 10 and the difference of the numbers is 8. Answer: The two numbers are 9 and 1.

### What do you mean by sum?

the aggregate of two or more numbers, magnitudes, quantities, or particulars as determined by or as if by the mathematical process of addition: The sum of 6 and 8 is 14. a particular aggregate or total, especially with reference to money: The expenses came to an enormous sum.

What is the addition of 1 to 10?

1 + 9 = 10 1 + 10 = 11
2 + 9 = 11 2 + 10 = 12
3 + 9 = 12 3 + 10 = 13
4 + 9 = 13 4 + 10 = 14

What is the sum of 9 and the difference of 3?

Back in numeric terms, the two numbers whose sum is 9 and whose difference is 3 are the numbers: 6 and 3.

#### What is the sum of two numbers is 16 and their difference is 2?

The sum of two numbers is 16 and their difference is 2 the big number between them is. Answer: 7 and 9. Thus numbers are 7 and 9. a+b=16 and a-b=2, therefor adding the 2 equations 2a=18, or a=9.

What is the sum of a number and 10?

Therefore, “the sum of a number and 10” can be written as: n + 10.

What does Sumsum mean?

Sum. more The result of adding two or more numbers. Example: 9 is the sum of 2, 4 and 3. (because 2 + 4 + 3 = 9). Drag the numerals to the two blue boxes to sum them:

## What number has a product of 9 and a sum of 10?

Question: What number has a product of 9 and a sum of 10? Answer: The two numbers are 1 and 9, because 1 times 9 is 9, and 1 added to 9 is 10.

How do you find the sum of n^2?

n^2. n2. There are several ways to solve this problem. One way is to view the sum as the sum of the first n n even integers. The sum of the first 2 n ( 2 n + 1) 2 − 2 ( n ( n + 1) 2) = n ( 2 n + 1) − n ( n + 1) = n 2. ) = n(2n+1)− n(n+ 1) = n2.